Autópsia Minimamente Invasiva (AMI) no serviço de verificação de óbitos do Ceará: possibilidades e avanços - Melo, Deborah Nunes de (2024)
Introduction: minimally invasive autopsy (MIA) is a viable alternative to conventional autopsy, considered the gold standard for determining the causes of death, in the various situations in which there is no possibility of opening the body after death. Arboviruses remain a serious public health problem in Brazil, with an increase in the number of deaths each year. However, there is limited capacity to investigate these deaths, even in places with technical resources to perform autopsies, such as death verification services, due to families' rejection of the procedure. Objective: To evaluate the potential use of Minimally Invasive Autopsy (AMI) for death surveillance in the state of Ceará. Methods: a partnership between the Ministry of Health, the Universities of São Paulo, the Federal University of Ceará and Barcelona, in addition to the Ceará Health Department and the Christus University Center, facilitated a practical theoretical course at the Ceará Death Verification Service where they were trained service pathologists. After this training, it was possible to propose, evaluate and validate a flow for implementing AMI in the SVO. Results: after training and reviewing the available literature, we showed the feasibility of performing AMI in the SVO in Ceará. A flow was established, and criteria were defined for the collection, identification, transport and storage of samples according to the diagnostic methodology to be used. Over a three-month period, 43 bodies underwent AMI at SVO. Of these, 21 (48.8%) were referred with a diagnostic hypothesis of an arbovirus and, in seven (16.3%) the diagnosis was confirmed (six of chikungunya; one of dengue); cases of covid-19 (n = 9), tuberculosis (n = 5), meningitis (n = 4), cryptococcosis (n = 1), Creutzfeldt-Jakob disease (n = 1), breast neoplasia (n = 1) were also confirmed. n = 1) and human rabies (n = 1). Finally, we report the confirmation of a pediatric death due to severe dengue that was possible due to the performance of AMI at the SVO in Ceará. Conclusion: the flow created and implemented allowed the capture of deaths suspected of arboviruses, in addition to the confirmation of other pathologies of interest to epidemiological surveillance. The technique appears to be promising for use in cases where conventional autopsy is not permitted by the family.